Chilean Pre-Service Teachers' Perceptions Towards Benefits and Challenges of EFL Writing Portfolios - Pamela Andrea Saavedra-Jeldres; Mónica Campos-Espinoza (Universidad Nacional de Colombia, 2019)
Although keeping writing portfolios has proved to be a successful strategy in developing writing skills in English as a foreign language, few studies have focused on pre-service teachers at the pre-intermediate level. This study aims to describe pre-service teachers' perceptions towards portfolio keeping. The sample consisted of 51 first-year students from an initial English language teacher education programme at a university in Southern Chile. A writing portfolio-based class was implemented over a seventeen-week period. Data were collected through an adapted questionnaire and a focus group conducted at the end of term. Results show that pre-service teachers value the strategy; they perceive they have improved their writing and reflection skills. They also draw attention to some challenges to be considered in the planning and implementation phases of the strategy.